A Downy Mildew Effector Attenuates Salicylic Acid–Triggered Immunity in Arabidopsis by Interacting with the Host Mediator Complex - Caillaud, Marie-Cecile (2013)
Plants are continually exposed to pathogen attack but usually remain healthy becausethey can activate defences upon perception of microbes. However, pathogens haveevolved to overcome plant immunity by delivering effectors into the plant cell toattenuate defence, resulting in disease. Recent studies suggest that some effectorsmay manipulate host transcription, but the specific mechanisms by which sucheffectors promote susceptibility remain unclear. We study the oomycete downy mildewpathogen of Arabidopsis, Hyaloperonsopora arabidopsidis (Hpa), and show here thatthe nuclear-localized effector HaRxL44 interacts with Mediator subunit 19a (MED19a),resulting in the degradation of MED19a in proteasome-dependent manner. TheMediator complex of ~25 proteins is broadly conserved in eukaryotes and mediates theinteraction between transcriptional regulators and RNA polymerase II. We foundMed19a to be a positive regulator of immunity against Hpa. Expression profilingexperiments reveal transcriptional changes resembling jasmonic acid/ethylene (JA/ET)signalling in the presence of HaRxL44, and also three days after infection with Hpa.Elevated JA/ET signalling is associated with a decrease in salicylic acid (SA)-triggeredimmunity (STI) in Arabidopsis plants expressing HaRxL44 and in med19a loss-offunctionmutants, whereas STI is elevated in plants overexpressing MED19a. Using aPR1::GUS reporter, we discovered that Hpa suppresses PR1 expression specifically incells containing haustoria, into which RxLR effectors are delivered, but not in nonhaustoriatedadjacent cells, which show high PR1::GUS expression levels. Thus,HaRxL44 interferes with Mediator function by degrading Med19, shifting the balance ofdefence transcription from SA-responsive defence to JA/ET-signalling, and enhancing susceptibility to biotrophs by attenuating SA-dependent gene expression.